Numerical Studies to Aid Interpretation of an Airborne VLF Resistivity Survey - Arcone,Steven A (1977)
Airborne resistivity surveys, which use the wavetilt phenomena of radiowaves, are used as a preliminary exploration technique to find suitable areas for either engineering investigations or geologic reconnaissance explorations. Survey results are usually presented as resistivity flight line profiles or as contour maps from which the interpretation or site selection process must be initiated. To aid in this process and provide additional understanding of the correlation between data obtained from airborne and ground surveys, an analysis was performed to determine a very-low- frequency airborne system's response to modelled resistivity anomalies assumed to occur at the surface of an idealized flat earth. Some of the assumptions used to simplify the analysis were based on the results of past surveys. The influences of survey altitude, anomaly size, and average ground resistivity upon airborne resistivity patterns were analyzed. The results show that the average resistivity of a region plays an important role in suppressing large resistivity contrasts for anomalies of approximately 1 sq. km. area. Curves are presented to separate the effects of resistivity contrast and anomaly size, and two examples are given to demonstrate how these curves may be applied to the results of actual surveys. (Author)